Optimasi Sifat Fisik Gel Variasi Konsentrasi Lidah Buaya dan Karbopol 940 dalam Pembuatan Basis Gel - Welni Rahmadani; Fitri Amelia (Lembaga Yasin AlSys, 2025)
Gel is a topical dosage form commonly used to treat acne, with carbopol 940 widely utilized as a gel base due to its ability to produce a clear gel with high viscosity at low concentrations (0.5–2%). This study aims to analyze variations in the concentrations of Aloe vera and carbopol 940 that result in a physically stable gel formulation. The gel was formulated using Aloe vera at concentrations of 1%, 2%, 3%, 4%, and 5%, and carbopol 940 at 0.5%, 1%, 1.5%, and 2%. Evaluation parameters included pH, adhesion, spreadability, and homogeneity tests. The results show that various combinations of Aloe vera and carbopol 940 produced gel preparations that met physical stability requirements, with the optimal formulation containing 0.5 grams of carbopol exhibiting good physical stability in terms of adhesion, spreadability, and homogeneity. These findings indicate the potential of Aloe vera and carbopol 940 as effective base ingredients for producing stable acne gel formulations that meet quality standards.